2022
DOI: 10.3389/fimmu.2022.838884
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Mediated Epigenetic Regulation of Rheumatoid Arthritis Susceptibility and Pathogenesis

Abstract: MicroRNAs (miRNAs) play crucial roles in regulating the transcriptome and development of rheumatoid arthritis (RA). Currently, a comprehensive map illustrating how miRNAs regulate transcripts, pathways, immune system differentiation, and their interactions with terminal cells such as fibroblast-like synoviocytes (FLS), immune-cells, osteoblasts, and osteoclasts are still laking. In this review, we summarize the roles of miRNAs in the susceptibility, pathogenesis, diagnosis, therapeutic intervention, and progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 123 publications
0
38
0
1
Order By: Relevance
“…The interaction between PDHB and NIMA-related kinase 10 ( NEK10 ) may be necessary for maintaining mitochondrial homeostasis, and NEK10 knockdown leads to increased mitochondrial damage and dysfunction ( 35 ). Thus, PDHB appears to be regulated by multiple miRNAs, while abnormalities in multiple miRNAs contribute to the pathological progression of RA, and the interconnection between the two deserves further exploration ( 36 ). In conclusion, downregulation of PDHB may contribute to the abnormal proliferative state of FLS in RA and may lead to defective Treg function through reduced binding to DJ-1.…”
Section: Relationship Between Cuproptosis and Ramentioning
confidence: 99%
“…The interaction between PDHB and NIMA-related kinase 10 ( NEK10 ) may be necessary for maintaining mitochondrial homeostasis, and NEK10 knockdown leads to increased mitochondrial damage and dysfunction ( 35 ). Thus, PDHB appears to be regulated by multiple miRNAs, while abnormalities in multiple miRNAs contribute to the pathological progression of RA, and the interconnection between the two deserves further exploration ( 36 ). In conclusion, downregulation of PDHB may contribute to the abnormal proliferative state of FLS in RA and may lead to defective Treg function through reduced binding to DJ-1.…”
Section: Relationship Between Cuproptosis and Ramentioning
confidence: 99%
“…MiRNA are a class of small non-coding RNAs molecules, around 22 nucleotides long, which regulate gene expression by binding specific sequences within target messenger RNA (mRNA). A large number of evidence demonstrated that some miRNA are differentially expressed in OA cartilage samples and synovial tissue of OA and RA patients, confirming their role in the development and progression of these pathological conditions [ 25 , 26 , 27 ]. Some of the dysregulated miRNA target genes encoding for proteins implicated in extracellular matrix remodeling, pro-inflammatory activities, and redox balance in OA chondrocytes and RA fibroblast-like synoviocytes [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AIM2 plays an important role in suppressing T cells involved in autoimmunity by reducing AKT-mTOR signaling and altering immune metabolism, which enhances Treg cell stability [ 35 ]. In addition, noncoding ribonucleic acid (RNA)s are closely associated with RA [ 36 , 37 ], and a Treg/ T helper 17 (Th17) cell imbalance is a common pathological factor in RA [ 3 ]. Long-stranded noncoding RNA nuclear enriched abundant transcript 1 ( NEAT1 ) affects the balance between Treg/Th17 cells by inhibiting AIM2 through the microRNA(miR)-485-5p sponge.…”
Section: Introductionmentioning
confidence: 99%